AKIBAT HUKUM PELANGGARAN KEWAJIBAN MENGGUNAKAN BAHASA INDONESIA DALAM PERJANJIAN DENGAN PIHAK ASING - Pasek Dwilaksmi, Ni Made Ayu (Acta Comitas : Jurnal Hukum Kenotariatan, 2020)
Indonesian is the national language as regulated in Act Number 24 of 2009. Therefore Indonesian language must be used for formal matters, one of which is in the context of the formulation of the agreement. In fact, in Indonesia there are agreements that use foreign languages, especially agreements involving foreign citizens in it. The purpose of writing this journal is to find out and analyze the arrangements regarding foreign language agreements in Indonesia and the legal consequences of violating the obligation to use the national language of Indonesia in agreements with foreign parties. This journal is doctrinal (normative) which uses a statutory and conceptual approach. Legal materials consist of primary and secondary legal materials which are then analyzed qualitatively. The conclusions that can be obtained in this journal include: (1) Arrangements regarding foreign language Act Number 24 of 2009 which basically stipulates that an agreement must use Indonesian language and must also use a foreign language rather than a foreign party. it originates; (2) Violation of the obligation to use Indonesian in an agreement with a foreign party is not regulated in Act Number 24 of 2009. However, if it is guided by the theory of interpretation of the legislation, namely a systematic interpretation, that the agreement that does not use Indonesian is a prohibited cause as referred to in Article 1320 and Article 1337 of the Civil Code. Therefore, the objective conditions in the agreement were not fulfilled and the agreement was considered null and void.